Critical Synthesis Package: Attribution Questionnaire-Short Form (AQ-27) - Daniel J Fridberg; Anthony O Ahmed (Association of American Medical Colleges, 2013)
Abstract This Critical Synthesis Package contains: (1) a Critical Analysis of the psychometric properties and application to health sciences education for the Attribution Questionnaire (AQ-27), (2) a copy of the AQ-27 instrument and scoring instructions developed by Patrick Corrigan, PhD. The AQ-27 is a 27-item, self-administered measure of stigmatizing attitudes and beliefs toward people with mental illness. The AQ-27 is divided into nine subscales with each subscale consisting of three questions. The nine subscales consist of: Blame, Anger, Pity, Help, Dangerousness, Fear, Avoidance, Segregation, and Coercion. Items are presented on a 9-point Likert-type scale, and subscale scores are calculated by summing the items corresponding to that subscale. A total score may be calculated as well. Higher factor scores represent greater endorsement of the corresponding attitude or belief. Studies have generally supported the reliability and validity of the AQ-27, although researchers disagree on the exact factor structure of the measure (six versus nine factors). The AQ-27 is sensitive to changes in public stigma toward mental illness following anti-stigma interventions, and has been used successfully in diverse adult samples, including healthcare students and professionals. There is a version for children, and a brief 9-item version which may be useful when administration time is a factor. However, comparatively less research has examined the psychometric properties of those measures. Future research should be conducted to further clarify the psychometric properties of the AQ-27 (e.g., factor structure) in diverse respondent samples.